ANALYSIS OF THE IMPLEMENTATION OF RISK MANAGEMENT ON BSI HASANAH CARD PRODUCTS: (Case Study at PT Bank Syariah Indonesia KC Medan Ahmad Yani) - REGINA YOLANDA SILALAHI (Journal of Finance, Economics and Business, 2023)
In accordance with sharia law and principles, Bank Syariah Indonesia issues cards called hasanah cards whose functions are similar to credit cards. The financing card product issued by PT Bank Syariah Indonesia has risks in its management. This research aims to determine the mechanism for issuing hasanah card products and to determine the application of risk management in reducing the risk of default or credit risk on hasanah cards at PT Bank Syariah Indonesia KC Medan Ahmad Yani. The method used in this research is a descriptive qualitative method. The data collection techniques that the author uses in this research are interviews and documentation observation. And the data used is primary data from interviews with Hasanah Card at BSI KC Medan Ahmad Yani and secondary data comes from books, journals, brochures and others. The results of this research state that the hasanah card issuance mechanism applies 3 contracts, namely kafalah, qardh and ijarah. The biggest risks are the risk of bad credit and irregularities in payments. However, in overcoming this risk, PT Bank Syariah KC Medan Ahmad Yani implements risk management, namely if there is a delay in payment for the Hasanah Card, a ta'widh fee will be charged, namely by setting a maximum benchmark fee based on the approved card limit, which is called a monthly fee. The nominal monthly fee is 1.75%. Islam prohibits taking profits in buying and selling transactions or lending and borrowing, the application of this hasanah card is in accordance with the National Sharia Fatwa (DSN) No.54/DSN-MUI/X/2006.) Implementation of risk management to reduce the risk of default on hasanah cards in Bank Syariah Indonesia is carried out using a process of risk identification, risk measurement, risk monitoring and risk control which is guided by the 5C principles of Character, Capacity, Capital, Collateral and Condition.